2015
DOI: 10.1242/jeb.125757
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid maturation of the muscle biochemistry that supports diving in Pacific walruses (Odobenus rosmarus divergens)

Abstract: Physiological constraints dictate animals' ability to exploit habitats. For marine mammals, it is important to quantify physiological limits that influence diving and their ability to alter foraging behaviors. We characterized age-specific dive limits of walruses by measuring anaerobic (acid-buffering capacity) and aerobic (myoglobin content) capacities of the muscles that power hind (longissimus dorsi) and fore (supraspinatus) flipper propulsion. Mean buffering capacities were similar across muscles and age c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 105 publications
1
17
0
Order By: Relevance
“…Independent juvenile walruses consume similar prey as adults (Fay ), but have a lower breath‐hold capacity (Noren et al . ) and less experience foraging than do adult walruses, putting them at a competitive disadvantage. Yet it is not clear why reduced access to food would have resulted in decreased juvenile survival (but not decreased calf production) in recent years, when it is thought to be the mechanism that resulted in decreased calf production (but not decreased juvenile survival) in the early 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…Independent juvenile walruses consume similar prey as adults (Fay ), but have a lower breath‐hold capacity (Noren et al . ) and less experience foraging than do adult walruses, putting them at a competitive disadvantage. Yet it is not clear why reduced access to food would have resulted in decreased juvenile survival (but not decreased calf production) in recent years, when it is thought to be the mechanism that resulted in decreased calf production (but not decreased juvenile survival) in the early 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…Censuring spurious foraging records is problematic because foraging in deep water has been reported with mature male Atlantic walruses (Born and Knutsen , Freitas et al ) and mature adult Pacific walruses may be able to engage in deep forage diving (Noren et al ). Noren et al () modeled the physiological aerobic dive potential of Pacific walruses based on measures of dive‐muscle oxygen stores and found that Pacific walrus aerobic diving is limited to depths <355 m. Further, they found that at depths >200 m, adult female walruses have <4 min of bottom time, which is more than a 60% reduction of modeled aerobic dive bottom time relative to diving over typical continental‐shelf foraging regions (≤80 m; Fay , Jay et al ). Based on Noren et al (), spurious foraging records may be censured when they occur in waters >355 m deep, but remain plausible when they occur at intermediate depths.…”
Section: Discussionmentioning
confidence: 99%
“…Noren et al () modeled the physiological aerobic dive potential of Pacific walruses based on measures of dive‐muscle oxygen stores and found that Pacific walrus aerobic diving is limited to depths <355 m. Further, they found that at depths >200 m, adult female walruses have <4 min of bottom time, which is more than a 60% reduction of modeled aerobic dive bottom time relative to diving over typical continental‐shelf foraging regions (≤80 m; Fay , Jay et al ). Based on Noren et al (), spurious foraging records may be censured when they occur in waters >355 m deep, but remain plausible when they occur at intermediate depths. We selected the behavioral track of an adult female to illustrate the potential of spurious foraging records.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations